Tourist Destination Management - As A Tool for the Formation of Competitive Advantages of the Region: Manajemen Destinasi Wisata - Sebagai Alat Pembentukan Keunggulan Kompetitif Daerah (Indonesian Journal of Cultural and Community Development, 2023)
The article analyzes the tourist destination as an element of the tourist system. Approaches to the definition of a tourist destination are considered. The features of the tourist destination as a tool for the formation of competitive advantages of the region are revealed.